Survival Benefit of Adjuvant Treatment with Huaier Granules Plus Lenvatinib in Hepatocellular Carcinoma Patients with Tumors Greater Than 5 cm After Radical Hepatectomy - Liu C; Bai Y; Bai Q; Parra MA; Zhao L; Zou J; Cao Q; Liu H; Yang H (Journal of Hepatocellular Carcinoma, 2025)
Cong Liu,1,2,* Ying Bai,3,* Qingquan Bai,4,5 Maria A Parra,6 Liangliang Zhao,7 Jiashu Zou,1 Qian Cao,1 Haoling Liu,8 Haiyan Yang1,6 1Hepatic and Liver Transplantation Division, Department of Surgery, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China; 2Department of Hepatobiliary Surgery, Weihai Central Hospital Affiliated to Qingdao University, Weihai, People’s Republic of China; 3Future Medical Laboratory, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China; 4Department of Hepatology & Gastroenterology, Charité Universitätsmedizin Berlin, Campus Virchow-Klinikum and Campus Charité Mitte, Berlin, 13353, Germany; 5Cancer Research Center, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 6Transplant Surgery Division, Department of Surgery, Johns-Hopkins Hospital, Baltimore, MD, USA; 7Department of Colorectal Surgery, First Affiliated Hospital of Harbin Medical University, Harbin, 150001, People’s Republic of China; 8The 2nd Endocrinology Division, Department of Internal Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haiyan Yang, Hepatic and Liver Transplantation Division, Department of Surgery, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China, Tel +86 15145009438, Email 101316@hrbmu.edu.cn Haoling Liu, The 2nd Endocrinology Division, Department of Internal Medicine, The First Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China, Tel +86 13633627146, Email liuhaoling@126.comBackground: The postoperative recurrence of hepatocellular carcinoma (HCC), influenced by various factors, including microvascular invasion (MVI), plays a critical role in the long-term prognosis following radical liver resection. This study investigated potential adjuvant treatment strategies for HCC patients who exhibit multiple recurrence factors after radical resection.Methods: A retrospective analysis was conducted on data from 243 patients who underwent radical resection for HCC and exhibited high recurrence factors at the First Affiliated Hospital of Harbin Medical University. Some of these patients received postoperative adjuvant therapy with Huaier granules, lenvatinib, or a combination of both, while others did not receive any postoperative adjuvant therapy.Results: Survival analysis showed a more favorable prognosis in the adjuvant Huaier granules and lenvatinib groups (all P < 0.05). Furthermore, when compared to monotherapy, the combination therapy group exhibited significantly improved overall survival (OS) (P = 0.001) and disease-free survival (DFS) (P = 0.001). Multivariate Cox regression analysis demonstrated that the addition of Huaier granules to lenvatinib was an independent protective factor associated with improved OS (hazard ratio (HR) = 0.777, 95% confidence interval (CI) = 0.616– 0.980, P = 0.033) and DFS (HR = 0.753, 95% CI = 0.615– 0.920, P = 0.006).Conclusion: In this retrospective analysis, the combination of Huaier granules and lenvatinib as postoperative adjuvant therapy was associated with improved long-term prognosis in patients at high risk of HCC recurrence.Keywords: hepatocellular carcinoma, Huaier granules, lenvatinib, recurrence, prognosis